A first course in econometric theory - Bacon, Robert William (Oxford [England] ; New York : Oxford University Press, 1988)
The author's approach in this text has been to stress the understanding of the technical details of the subject at the expense of generality, in the belief that if we really understand the simplest cases then we can hope to progress to general cases without loss of comprehension. The book is a reflection of the author's several years' teaching econometric theory to undergraduates.
Includes index.
rpm 13/09/2017
Loans
Keywords: Econometrics